Study of Fe, Co, and Mn-based perovskite-type catalysts for the simultaneous control of soot and NOX from diesel engine exhaust. (December 2017) - Dhal, Ganesh Chandra; Dey, Subhashish; Mohan, Devendra; Prasad, Ram
Graphical abstract: Abstract: This paper discusses, the nanometric size effects, including intrinsic factors such as structure, the nature of A-site ion substitution, B-site ions, on the redox properties of nanometric La1−x Kx FeO3, La1−x Kx CoO3, La1−x Nax MnO3, La1−x Kx MnO3, perovskite-type oxide catalysts. The external factors of catalyst and soot particulate, the content of NO and O2 and the ratio of catalyst and gas flow rate on the catalytic activity for the simultaneous removal of NOX and soot particulates were systematically investigated. The catalysts were characterized by means of SEM, EDX, XRD and FT-IR and the catalytic potential for the simultaneous removal of nitrogen oxides (NOx) and diesel particulate matter (soot) were evaluated by temperature-programmed oxidation reactions. The entire catalyst samples obtained the perovskite structure, with high activities for the simultaneous elimination of soot and NOX . Alternatively, the number of surface atoms is much higher than the normal bulk catalysts and the size of the nanoparticle is also smaller. These characteristics are beneficial for the adsorption and activation of reactant molecules including NO or O2, or even soot particle.